TRANSGENDER PROTECTION ACT - ANALYSIS ON LACUNA IN IT. - Nair, Lakshmi; P., Lakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Transgender Persons (Protection of Rights) Act, 2019, was enacted to protect the rights and dignity of transgender individuals in India. While the Act aims to address critical issues such as discrimination, education, employment, and healthcare, it has faced criticism for perceived inadequacies and inconsistencies in addressing the community’s needs. This study critically analyzes the Act, focusing on its provisions, implementation challenges, and the gaps that undermine its effectiveness. Drawing from legal analyses, case studies, and inputs from the transgender community, the research aims to provide actionable recommendations to address these lacunas, ensuring the Act better aligns with the principles of equity and social justice.